Biological Control of Fusarium Wilt on Tomato Using Avirulent Fusarium oxysporum f. sp. cepae Combined with Siam Weed Compost - Nugroho, Bambang; Mildaryani, Warmanti; Astriani, Dian (Universitas Gadjah Mada, 2025)
Fusarium wilt caused by Fusarium oxysporum f. sp. lycopersici is a major disease that results in significant yield loss in tomato production. Currently, chemical control of Fusarium wilt using fungicides has yielded unsatisfactory results and has caused negative effects. Biological control using antagonistic microorganism combined with compost is a promising and environmentally friendly alternative management method for this disease. This research aimed to evaluate the effectiveness of an avirulent Fusarium oxysporum f. sp. cepae biological agent combined with siam weed compost to manage Fusarium wilt and increase growth and yield in tomato productions. This research was conducted using a completely randomized design with two factors and three replicates. The first factor was the dose of the avirulent F. oxysporum f. sp. cepae biological agent i.e 0 (control), 80, and 100 mL/plant. The second factor was dose of siam weed compost i.e. 0 (control), 300, and 600 g/plant. Disease intensity, plant growth and yield variables were evaluated. Data collected were analyzed using an ANOVA followed with Duncan’s Multiple Range test at 95% confidence level. The results showed that the use of avirulent F. oxysporum f. sp. cepae biological agent was able to manage Fusarium wilt disease in tomato productions and increase growth and yield of tomato. The best treatment for increasing tomato yield was the combination of 100 mL/plant of avirulent F. oxysporum f. sp. cepae with 600 g/plant of siam weed compost, resulting in a yield of 110.41 g/plant.